Ilham Ceramics: Bracing Through the Covid-19 Storm - Abd Ghani, Nor Farzana; Mahmod, Musyrifah (2022)
This is the case of Ilham Ceramics, a local crafter in Langkawi. The case discusses the scenario of its business situation during the Covid-19 pandemic circa early 2020 until October 2021. The business was facing problems due to the lockdown in 2020 since the business relies on tourists inbound to Langkawi. To overcome this, the Government is moving towards promoting the concept of Digital Economy amongst local businesses in order to embark on E-Commerce. Goods can be traded online on popular online marketplace, imitating the successfulness of Shoppee, Lazada, eBay and the likes. With the initiatives from the government to support the local crafters and Ilham Ceramics’ own initiatives, would the business be able to survive after the Covid-19 storm? Could E-Commerce be the perfect solution to help the business survive during and post pandemic?